2017
DOI: 10.1021/acs.est.7b00826
|View full text |Cite
|
Sign up to set email alerts
|

Toward Quantitative Understanding of the Bioavailability of Dissolved Organic Matter in Freshwater Lake during Cyanobacteria Blooming

Abstract: Occurrence of cyanobacterial harmful algal blooms (CyanoHAB) can induce considerable patchiness in the concentration and bioavailability of dissolved organic matter (DOM), which could influence biogeochemical processes and fuel microbial metabolism. In the present study, a laboratory 4-stage plug-flow bioreactor was used to successfully separate the CyanoHAB-derived DOM isolated from the eutrophic Lake Taihu (China) into continuum classes of bioavailable compounds. A combination of new state-of-the-art tools b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(52 citation statements)
references
References 50 publications
(126 reference statements)
3
45
0
Order By: Relevance
“…Consistent with the results of Thieme et al (2019) in conifer species (Picea abies and P. sylvestris), the lignin/CRAM-like structures accounted for the largest proportion of DOM, followed by tannin-like structures (Figure 3). This soil DOM composition is consistent with the chemical composition of Chinese fir litter, which mainly comprise lignin, tannin, and resin (Bai et al, 2017). During decomposition of leaf litter, loss of labile compounds (e.g., carbohydrates and amino acids) occurs, and the dominance of lignin-like structures increases (Bai et al, 2017).…”
Section: Characterization Of Dissolved Organic Matter Chemodiversitysupporting
confidence: 79%
“…Consistent with the results of Thieme et al (2019) in conifer species (Picea abies and P. sylvestris), the lignin/CRAM-like structures accounted for the largest proportion of DOM, followed by tannin-like structures (Figure 3). This soil DOM composition is consistent with the chemical composition of Chinese fir litter, which mainly comprise lignin, tannin, and resin (Bai et al, 2017). During decomposition of leaf litter, loss of labile compounds (e.g., carbohydrates and amino acids) occurs, and the dominance of lignin-like structures increases (Bai et al, 2017).…”
Section: Characterization Of Dissolved Organic Matter Chemodiversitysupporting
confidence: 79%
“…In the lability test experiment, we found that heterotrophs could indeed consume the majority of ionizable cyanobacteria‐derived DOM within less than 2 d. Most of the peaks removed by bacterial degradation were located in the labile region of the van Krevelen diagram, confirming the fast turnover of the aliphatic material (D'Andrilli et al 2015). Contrarily to Bai et al 2017, saturated compounds were preferentially transformed and removed below the detection limit for peak identification along with the most hydrophilic and hydrophobic species, as shown in Fig. 3.…”
Section: Discussionmentioning
confidence: 94%
“…This does not include polysaccharides and proteins, which have previously been characterized in extracellular mixtures from cyanobacteria, including M. aeruginosa (Myklestad 2005; Pivokonsky et al 2014). Instead, our study focuses on the ionizable metabolite portion (Bittar et al 2015 a ; Bai et al 2017; Powers et al 2019), with a view to assessing the importance of this autochthonous material in studies that use a similar analytical pipeline to characterize freshwater DOM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, bioavailable phosphorus could be supplemented when required by enzymatic hydrolysis of EHP. There are numerous nutrient supplementation pathways for freshwater lakes, such as nitrogen fixation from the atmosphere (Jean, Cassar, Setzer, & Bellenger, ), release of nutrients from sediments (Cao, Wang, He, Luo, & Zheng, ; Ding et al., , ), and microbial activity (Bai et al., ). Recent study indicated that Fe‐P‐S system in water–sediment interface has great impacts on phosphorus circulation in aquatic systems (Chen et al., ).…”
Section: Resultsmentioning
confidence: 99%